KARAKTER TOKOH DALAM NOVEL LANGIT MEKAH BERKABUT MERAH KARYA GEIDURRAHMAN AL-MISHRY BERBASIS NILAI-NILAI KARAKTER RELIGIUS DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA DI MADRASAH ALIYAH - Aida Azizah; Leli Nisfi Setiana (Universitas Muria Kudus, 2017)
Novel Langit Mekah Berkabut Merah work is a novel that has a lot of wisdom about religious values. Religious value of these figures seen in the overall story is actualized through the elements of the literary works of the builders. Author of the novel tells the story using language that is easy to understand and use easily understandable story line. The background of the story in the novel is parallel to the background of the life of the students, so that religious values can be utilized in the teaching of literature in class XII SMA / MA.